Differential Alteration in Expression of Striatal GABAAR Subunits in Mouse Models of Huntington’s Disease - Du, Zhuowei; Tertrais, Margot; Courtand, Gilles; Leste-Lasserre, Thierry; Cardoit, Laura; Masmejean, Frédérique; Halgand, Christophe; Cho, Yoon H.; Garret, Maurice (Frontiers in Molecular Neuroscience, 2017)
Huntington’s disease (HD) is a neurodegenerative disorder characterized by progressive motor symptoms that are preceded by cognitive deficits and is considered as a disorder that primarily affects forebrain striatal neurons. To gain a better understanding of the molecular and cellular mechanisms associated with disease progression, we analysed the expression of proteins involved in GABAergic neurotransmission in the striatum of the R6/1 transgenic mouse model. Western blot, quantitative PCR and immunohistochemical analyses were conducted on male R6/1 mice and age-matched wild type littermates. Analyses were performed on 2 and 6 month-old animals, respectively before and after the onset of motor symptoms. Expression of GAD 67, GAD 65, NL2, or gephyrin proteins, involved in GABA synthesis or synapse formation did not display major changes. In contrast, expression of α1, α3 and α5 GABAAR subunits was increased while the expression of δ was decreased, suggesting a change in tonic- and phasic inhibitory transmission. Western blot analysis of the striatum from 8 month-old Hdh Q111, a knock-in mouse model of HD with mild deficits, confirmed the α1 subunit increased expression. From immunohistochemical analyses, we also found that α1 subunit expression is increased in medium-sized spiny projection neurons (MSN) and decreased in parvalbumin (PV)-expressing interneurons at 2 and 6 months in R6/1 mice. Moreover, α2 subunit labelling on the PV and MSN cell membranes was increased at 2 months and decreased at 6 months. Alteration of gene expression in the striatum and modification of GABAA receptor subtypes in both interneurons and projection neurons suggested that HD mutation has a profound effect on synaptic plasticity at an early stage, before the onset of motor symptoms. These results also indicate that cognitive and other behavioural deficits may be associated with changes in GABAergic neurotransmission that consequently could be a relevant target for early therapeutic treatment.